CREATIVE ECONOMIC GOVERNANCE IN TANJUNG MEDANG VILLAGE - Randi Randi (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
The limitations of village communities in managing the creative economy mean that the available potential in the village could not improve the economy of the village community, especially village income. The large potential of rivers, pineapples and rubber plantation products do not make the people of Tanjung Medang village economically prosperous, Based on data from the Ministry of Social Affairs, the number of underprivileged families or PKH (conditional cash transfer programme) beneficiaries in the village of Tanjung Medang is 185. This article is aimed at assisting Creative Economy Governance in Tanjung Medang Village (A Study on Village-Owned Enterprises or BUMDes). Tanjung Medang Village has experienced problems in developing creative economic governance and utilizing the village's potential as a village tourist destination. Through the documentary study and observations in the village, the people of Tanjung Medang village might improve the village economy through BUMDes. In addition, this problem could be used to increase the income of the village communities and create village tourist destinations. The method of the study is a qualitative analysis method with descriptive data presentation of literature review.